2021
DOI: 10.24203/ijcit.v10i2.79
|View full text |Cite
|
Sign up to set email alerts
|

Research Methods in Machine Learning: A Content Analysis

Abstract: Research methods in machine learning play a pivotal role since the accuracy and reliability of the results are influenced by the research methods used. The main aims of this paper were to explore current research methods in machine learning, emerging themes, and the implications of those themes in machine learning research.  To achieve this the researchers analyzed a total of 100 articles published since 2019 in IEEE journals. This study revealed that Machine learning uses quantitative research methods with ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 110 publications
1
16
0
Order By: Relevance
“…Most studies did not mention the selection process of algorithms, and LR was the most frequent machine learning algorithm, followed by RF, SVM, NN, and DT. These results match the study by Kamiri and Mariga [52].…”
Section: Machine Learning Prediction Models Of Pressure Injurysupporting
confidence: 93%
See 1 more Smart Citation
“…Most studies did not mention the selection process of algorithms, and LR was the most frequent machine learning algorithm, followed by RF, SVM, NN, and DT. These results match the study by Kamiri and Mariga [52].…”
Section: Machine Learning Prediction Models Of Pressure Injurysupporting
confidence: 93%
“…It is worth mentioning that there is one study that utilized the experimental design to construct the prediction model of pressure injury. This approach matches a content analysis study by Kamiri and Mariga [52] to discuss the research methodology in machine learning, which revealed that all studies included in the analysis used machine learning in experimental designs.…”
Section: Characteristics Of Included Studiesmentioning
confidence: 87%
“…Kamiri & Mariga [ 9 ] suggested, that ML is a subfield of artificial intelligence that deals with the creation of algorithms and procedures that allow a computer to learn and gain intelligence through experience. The research methodology used in machine learning research is critical because it influences the accuracy and dependability of the results.…”
Section: Methodsmentioning
confidence: 99%
“…Kamiri and Mariga [ 17 ] suggested that ML is a subfield of artificial intelligence that deals with the creation of algorithms and procedures that allow a computer to learn and gain intelligence through experience. The research methodology used in ML research is critical because it influences the accuracy and dependability of the results.…”
Section: Literature Reviewmentioning
confidence: 99%